Knowledge management and the development of top management leader (مجلة المنصور, 2022)
We are living in the time of science and technology. The person who has the Knowledge, and don't have the ability to manage and transform it in effective way in performance with the best way, will not be able to face the challengesand the competition's risks for self-steam. Especially with the beginning of the third millennial, and dominating information economy or knowledge dependent economy. So, having and acquiring information and knowledge becomes insufficient.Therefore, the importance of talk about managing knowledge and its role in developing and preparing managerial leaders is considered one of the important issues that the society-institutions are seeking for equally in private and public sector to provide and efficient characteristics to enable it for competing and achieving the best in the middle of a global informationeconomy. The content of the challenge in this time is the existence a national intelligent capital.So this paper is trying to focus mainly or showing the important challenges for the knowledgeable informative economy in the digital time , it obliges the necessity of taking care for developing national information capital in order to improve the organizational performance with a future sight the range of implementing information managements programs to prepare and developseffective managerial leaders who participate to develop (raise) the institutional performance level that will reflect , of course , upon the national economy.